Evaluation and Production of Cellulases from Aspergillus Niger Using Diverse Agro-Waste Substrates (Journal of Asian Development Studies, 2025)
The study focused on optimizing cellulase production from Aspergillus niger, evaluating its enzyme activity against various agro-waste substrates, including corn cobs (Zea mays), orange peel (Citrus sinensis), sugarcane bagasse (Saccharum officinarum), wheat bran (Triticum aestivum), and wheat straw (Triticum aestivum). The highest cellulase activity, measured using CMCase, was observed with corn cob (0.68 U/mL), followed by orange peel (0.41 U/mL), sugarcane bagasse (0.35 U/mL), and wheat bran (0.17 U/mL). No visible fungal growth was observed on wheat straw. In the filter paper assay, orange peel exhibited the highest enzyme activity among all substrates (0.39 U/mL), followed by corn cob (0.32 U/mL), sugarcane bagasse (0.28 U/mL), and wheat bran (0.17 U/mL). This study showed the potential of agro-wastes as valuable substrates for industrial enzyme production, with Aspergillus niger proving effective in utilizing these materials for cellulase production.